2006
DOI: 10.1111/j.1467-9868.2006.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Likelihood Confidence Regions in a Partially Linear Single-Index Model

Abstract: Empirical-likelihood-based inference for the parameters in a partially linear single-index model is investigated. Unlike existing empirical likelihood procedures for other simpler models, if there is no bias correction the limit distribution of the empirical likelihood ratio cannot be asymptotically tractable. To attack this difficulty we propose a bias correction to achieve the standard "χ"-super-2-limit. The bias-corrected empirical likelihood ratio shares some of the desired features of the existing least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
133
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(133 citation statements)
references
References 37 publications
0
133
0
Order By: Relevance
“…At present, the estimation problems of the single-index model have been widely studied. For instance, Ichimura [1] studied the properties of semiparametric least-squares estimators in general single-index model; Härdle and Tsybakov [2] developed the average derivative method to obtain the estimators of the index vector; Yu and Ruppert [3] proposed P-spline estimation for partially linear single-index models and studied asymptotic properties of the penalized least square estimators; Zhu and Xue [4] investigated empirical-likelihood-based inference for the parameters in a partially linear single-index model, they defined a bias-corrected empirical log-likelihood ratios and obtained the standard χ 2 distribution as its asymptotic distribution; Carroll et al [5] studied generalized partially linear single-index models; Xia et al [6] explored an extended version of a generalized partially linear single-index model.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the estimation problems of the single-index model have been widely studied. For instance, Ichimura [1] studied the properties of semiparametric least-squares estimators in general single-index model; Härdle and Tsybakov [2] developed the average derivative method to obtain the estimators of the index vector; Yu and Ruppert [3] proposed P-spline estimation for partially linear single-index models and studied asymptotic properties of the penalized least square estimators; Zhu and Xue [4] investigated empirical-likelihood-based inference for the parameters in a partially linear single-index model, they defined a bias-corrected empirical log-likelihood ratios and obtained the standard χ 2 distribution as its asymptotic distribution; Carroll et al [5] studied generalized partially linear single-index models; Xia et al [6] explored an extended version of a generalized partially linear single-index model.…”
Section: Introductionmentioning
confidence: 99%
“…Now, let Rn(β (r) ) be the EL ratio obtained by replacing the ξ i 's by η i 's. Then, Zhu and Xue (2006) showed that Wilks' theorem holds, i.e.…”
Section: Single-index Regression Modelmentioning
confidence: 99%
“…The classical bias corrections in literature are used. Section 3 expatiates the results on the partially linear single-index model to describe the new bias correction proposed in Zhu and Xue (2006). Section 4 summarizes the results on the partial linear model with longitudinal data, and Section 5 presents the bias correction method for the varying coefficient model with longitudinal data.…”
Section: Introductionmentioning
confidence: 99%